A Model of an Optimum Currency Area - Ricci, Luca (IMF Working Papers; Working Paper ;, 1997)
This paper investigates the circumstances under which it is beneficial to participate in a currency area. A two-country monetary model of trade with nominal rigidities encompasses the real and monetary arguments suggested by the optimum currency area literature: correlation of real shocks, international factor mobility, fiscal adjustment, openness, difference in national inflationary biases, correlation of monetary shocks, and benefits of a single currency. The effect of openness on the net benefits is ambiguous, contrary to the usual argument that more open economies are better candidates for a currency area. Countries do not necessarily agree on whether a given currency union should be created.